Folate and Vitamin B12 in The Irish Longitudinal Study on Ageing cohort: associations with cognitive function - O'Connor, Deirdre (Trinity College Dublin. School of Medicine. Discipline of Medical Gerontology, 2024)
The aim of this Ph.D. thesis is to examine nutrition, cognitive and autonomic dysfunction in the older population in Ireland. One review and five separate quantitative studies are presented in this thesis, which use data from The Irish Longitudinal Study on Ageing (TILDA), a large population representative cohort study of adults over the age of 50 residing in Ireland. The thesis focuses on the relationship between folate and vitamin B12 with cognitive dysfunction and commonly observed manifestations of autonomic dysfunction - orthostatic hypotension (OH). Nutritional behaviour among the population in the form of compliance with national food-based dietary guideline (FBDGs) are also examined. Chapter summaries: Background and Literature Review Chapter One provides an overview of the background literature related to public health nutrition changes, technological advancements, and the impact on the ageing population. It introduces the role of the B-vitamins folate and vitamin B12in maintaining metabolic function and discusses the "methylfolate trap hypothesis" that suggests vitamin B12 deficiency impairs overall folate metabolism. The chapter also examines the nutritional behaviours of older adults in Ireland. Chapter Two reviews the existing evidence on the relationships between folate, vitamin B12, and cognitive function, and blood pressure control (as an indicator of autonomic function) in older adults. It reviews studies examining the role of folate and vitamin B12 in cognitive dysfunction and blood pressure control among older adults. Methodology Chapter Three gives an overview of the methodologies employed in TILDA, provides a detailed description of the data acquisition across the longitudinal 2 elements of the study, and describes the measures used in each of the individual studies that make up this thesis. Five Quantitative Studies Chapter Four presents the first empirical study of the thesis, which aims to quantify plasma folate and vitamin B12 status in a nationally representative population of older adults in Ireland. It determines the prevalence of low status and deficiency rates of folate and vitamin B12 and investigates the factors influencing these vitamin concentrations. Chapter Five presents the second empirical study, which investigates the cross-sectional associations between folate, vitamin B12, and two tests of global cognitive function in older adults. It tests the hypothesis that lower concentrations of folate and vitamin B12 are associated with poorer cognitive health. Chapter Six focuses on the third empirical study, which examines the longitudinal associations between folate concentrations and changes in several domain of cognitive performance over eight years. It investigates the hypothesis that low folate status is associated with accelerated cognitive decline over time. Chapter Seven presents the fourth empirical study of my thesis, which investigates the cross-sectional and longitudinal associations between plasma folate, vitamin B12 concentrations, and orthostatic hypotension (OH) in older adults. It examines the hypothesis that low levels of folate and vitamin B12 may increase the risk of OH. Chapter Eight focuses on the fifth and final empirical study, which aims to describe and summarise the consumption frequencies and compliance levels of food groups as defined by national dietary recommendations. It examines the dietary patterns and adherence to food guidelines among older adults in Ireland. Discussion and Conclusions Chapter Nine provides a discussion of the main findings of the thesis and their implications. It summarises the key findings from each empirical study and their contribution to the overall understanding of the relationships between folate, vitamin B12, cognitive function, orthostatic hypotension, and adherence to dietary guidelines in older adults. The chapter concludes by highlighting the need for age-specific and sustainable nutritional guidance for older adults. Overall, the thesis investigates the associations between folate, vitamin B12, cognitive function, orthostatic hypotension, and dietary patterns in older adults, providing valuable insights into the role of nutrition in ageing and important health outcomes.
APPROVED